2011
DOI: 10.1186/1477-7827-9-108
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces LH, 17 beta-estradiol and induces differential regulation of sex steroid receptors in reproductive tissues during rat ovulation

Abstract: BackgroundMelatonin is associated with direct or indirect actions upon female reproductive function. However, its effects on sex hormones and steroid receptors during ovulation are not clearly defined. This study aimed to verify whether exposure to long-term melatonin is able to cause reproductive hormonal disturbances as well as their role on sex steroid receptors in the rat ovary, oviduct and uterus during ovulation.MethodsTwenty-four adult Wistar rats, 60 days old (+/- 250 g) were randomly divided into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 58 publications
5
47
0
3
Order By: Relevance
“…The mechanisms by which melatonin may influence the expression of the uterine steroid receptors are not easy to understand since no references about a direct action of melatonin at the uterine level through specific receptors in the reproductive tract of the sheep have been reported. However, Zhao et al (2002) characterized the melatonin receptor (MT 1 ) transcript in rat endometrium during oestrous cycle, and more recently, Chuffa et al (2011) described that the expression of MT 1 is up-regulated by the melatonin treatment and is associated with the down-regulation of the ER-beta and PRB in the reproductive tissue of rats.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which melatonin may influence the expression of the uterine steroid receptors are not easy to understand since no references about a direct action of melatonin at the uterine level through specific receptors in the reproductive tract of the sheep have been reported. However, Zhao et al (2002) characterized the melatonin receptor (MT 1 ) transcript in rat endometrium during oestrous cycle, and more recently, Chuffa et al (2011) described that the expression of MT 1 is up-regulated by the melatonin treatment and is associated with the down-regulation of the ER-beta and PRB in the reproductive tissue of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, melatonin at doses of 200 µg/100 g of BW/day induced longer estrous periods and reductions in ovarian weight [43]. Our previous reports suggested that long-term mel treatment satisfactorily reduces ovarian lipoperoxidation and plasma estradiol levels, while enhancing tissue antioxidant defenses [27], [28]. Moreover, mel treatment was also associated with lower ovarian weights and estrous cycle synchronization [44].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of these receptors is up-regulated by the melatonin treatment and is associated with the down-regulation of the ER-beta and PRB (Chuffa et al, 2011). Influence of the melatonin on the incidence of endometrial cancer has been suggested (Sandyk et al, 1992) and the presence of the functional MT2 receptor was detected in the estrogen positive cell line derived from patient with endometrial carcinoma (Kobayashi et al, 2003).…”
Section: Melatonin Receptors In the Reproductive And Gestational Tmentioning
confidence: 99%